Lived Religion and Social Cohesion: Symbolic Meanings of Sa-uyunan Muharam in Sundanese Community - Dadang Kuswana; Muhamad Hilmi Pauzian (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
The tradition of Sa-uyunan Muharam is a unique phenomenon in the Indonesian Islamic landscape that shows the integration of Islamic values with Sundanese cultural wisdom to build social cohesion. This research aims to analyze the symbolic meaning of the Sa-uyunan Muharam tradition and examine its contribution to the harmony of Sundanese society. Using a qualitative ethnographic approach with symbolic anthropological theory, the concept of lived religion, and collective memory theory, data were collected through participatory observation, in-depth interviews with 17 intergenerational informants, and documentation. The results of the study reveal four main symbolic systems: the practice of pilgrimage as spiritual continuity, the distribution of food as a symbol of solidarity, the torch parade as the light of faith and unity, and the distribution of gifts as a manifestation of collective justice. The philosophy of sa-uyunan operates through deliberation, mutual cooperation, and friendship that creates horizontal and vertical social integration. This tradition demonstrates the models of "institutional lived religion" and "adaptive traditionalism" that contribute significantly to the harmony of society as a mechanism of multidimensional social integration, markers of collective identity, and strategies of cultural resilience.